THE LEGENDS OF TWO BROTHERS IN TAMIL NADU (International Journal of Food and Nutritional Sciences, 2022)
In general, Tamil Nadu's Sivagangai Seemai is an important region. The present-day kingdoms of Ramnathapuram, Sivagangai, and Pudukottai were all part of the Ramnathapuram Realm. Fearless and brave leaders like Sasivarna Thevar, Raja Muthu Vaduganatha Peria Oodayar Thevar, Rani Velu Nachiar, and the Maruthu siblings led the Sivagangai region.By the end of the seventeenth century, the Maruthu siblings had taken over management of the Sivaganga region. The Maruthu Siblings used the "Go Sangam" dissident group as a front. Oomathurai was released from prison due to this rebel organisation. The British Government were enraged with the Marudhu siblings as a result of this incident. A decree known as the "Jambu Deepa Decree" was recorded by the Maruthu siblings on June 16th, 1801. He invited everyone, regardless of status or background, to join one group in this decree.